Response of rat lung to tobacco smoke condensate or fractions derived from it administered repeatedly by intratracheal instillation. - Davis, B. R. (Nature Publishing Group, 1975)
The repeated intratracheal instillation of cigarette smoke condensate (SWS) in rats at close to maximum tolerated dose levels failed to induce squamous neoplasms in the lungs although such treatment was associated with an increased incidence of cuboidal/columnar metaplasia (CCM) and squamous metaplasia (Sq.M) of alveolar epithelium. With one exception, various fractions of SWS had no effect on lung tumour incidence though some were more effective than SWS in increasing the incidence of CCM and Sq.M. The exceptional fraction, Fraction P, which contains most of the polycyclic aromatic hydrocarbons of smoke and is the most effective of the fractions tested in producing tumours in mouse skin, gave rise to 4 squamous tumours of doubtful malignancy and one metastasizing squanmous carcinoma among 3 groups of 18 animals exposed at 3 different dose levels. The results are discussed in relation to the possible development of a method for comparing condensates for relative lung carcinogenicity. IMAGES: